Evaluating Psychometric Properties of the Stress Measurement Instrument (the Operational and Organizational Police Stress Questionnaires) with the Application of Rasch Model in the Indonesian Nasional Police (INP) - Argo, Abi Risa Bayu; Yulianto, Heri; Nuryanto, Dwi (JP3I (Jurnal Pengukuran Psikologi dan Pendidikan Indonesia), 2021)
Police Stress Questionnaire (PSQ) is a questionnaire developed by McCreary and Thompson (2006) to measure stress exercised by the police. The development of this questionnaire is based on the reason that the previous stress measuring instruments only measure general stressors and can’t describe specific stressors, especially in types of work that exert high level of stress. This study aims to evaluate the Police Stress Questionnaire (PSQ) instrument consists of two instruments, namely the Operational Police Stress Questionnaire (PSQ-Op) and the Organizational Police Stress Questionnaire (PSQ-Org), each containing 20 items with seven-point Likert scale for police officers in Indonesia. Respondents in this study were 313 police officers who served in the National Police Headquarters work unit (32.9%), Regional Police (38.3%), Resort Police (19.5%) and Sector Police (9.3%). The data collection technique used non-probability sampling with the help of the google form application. The method used is the Rating Scale Model (RSM). The results show that the Indonesian version of the Police Stressor Questionnaire (PSQ) is proven to meet unidimensional assumptions and the reliability analysis for person and items shows a strong level of reliability. However, the Rasch RSM analysis found violations of the assumption of local independence and problematic discrimination at specific thresholds (threshold disorder) in the seven response categories used. Furthermore, the results of the application of the Rasch Model Rating Scale model show that the psychometric facts of the two research instruments are very good and precise, as well as the suitability of the items to the model. Implications and suggestions for future research are also presented in the discussion.